A comparison of endoscopic and microscopic techniques for the repair of tympanic membrane perforations - Güler, İsmail; Özcan, Müge (ENT Updates, 2019)
Objective: This study aims to compare endoscopic and microscopic tympanoplasty in terms of graft success rate and hearing gain. Methods: Medical records of 236 patients (99 females and 137 males) aged 18 to 74 years with chronic otitis media who underwent myringoplasty, between January 2014 and June 2017 were retrospectively compared. Patients were divided into two groups; microscopic myringoplasty (140 patients), endoscopic myringoplasty (96 patients). Demographic data, pure tone audiometric results preoperatively and 6 months postoperatively, operation time, hearing gain and graft success rate were evaluated. Results: The mean operation time was 57.8±9.6 minutes for the endoscopic group and 78.6±17.7 minutes for the microscopic group (p<0.001). The mean preoperative airbone gap (ABG) was 24.1±11.5 dB for the microscopic group and 22.7±9.2 dB for the endoscopic group, whereas the mean postoperative ABG was 11.6±9.9 and 9.8±9.3 dB respectively. Graft success rate was 90.3% (213 patients) for entire group, 89.7% (131 patients) for the microscopic group, and 91.1% (82 patients) for the endoscopic group (p=0.727). The functional success rate (ABG≤10 dB) was 72.5% (171 patients) in the entire group. The mean hearing gain was 12.4±10.8 and 12.8±9 dB in the microscopic and endoscopic groups respectively. Conclusion: Endoscopic technique offers similar graft success and hearing outcomes to microscopic technique along with a shorter operation time.